Axial coordination of pyridyl-containing pentacenes to porphyrins - Waterloo, Andreas; Lippert, Rainer; Jux, Norbert; Tykwinski, Rik (Journal of Coordination Chemistry, 2015)
A pair of pentacenes that are functionalized in the 6-position with either a 3- or 4-pyridyl group via a triazole linker have been used to form complexes with a tetra(aryl)ruthenium(II) porphyrin through axial coordination. The pentacene–porphyrin dyads 5 and 6 have been structurally characterized through a combination of spectroscopic techniques. UV–vis spectroscopy shows that the absorption profiles of the two chromophores, the porphyrin and the pentacene, are complementary, providing absorptions throughout the UV and visible regions. While the dyads are reasonably stable in the solid state under ambient conditions they are, unfortunately, only stable in solution for hours when exposed to light and air.
EAM Import::2019-03-13